On-the-go tropical soil sensing for pH determination using ion-selective electrodes - Silva, Fernanda Cristina de Souza; Molin, José Paulo (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to assess the performance of an antimony ion-selective electrode (ISE) sensor system, using manual and automatic operating modes, for measuring the potential of hydrogen (pH), in real time, in Oxisols with different characteristics. Samples were manually collected and sent to a laboratory for determination of pH in water and calcium chloride, whose values were used as references. Another set of samples was also automatically collected using a commercial equipment, and readings were performed in manual mode. The performance parameters of the sensor system were calculated and evaluated. Part of the soil samples was used to assess the degree of influence of moisture in determining pH. Calibration lines were constructed. The statistical analysis revealed better results for the manual mode. Both modes of operation had errors superior to those accepted as a limit in laboratory techniques, however, with the possibility of high data density and with positive and promising results. Soil moisture interfered with the result of the readings. The sensor system yields a sampling density of 45 data per hectare, which represents a great contribution to the intensification of data for a better spatial evaluation of soil information.